The Impact of Labour Market Reform Policies on Insiders' and Outsiders' Low-Wage Risk - Marco Giesselmann (European Sociological Review, 2014)
Taking a cross-national comparative perspective, this study analyses differences in individual determinants of the low-wage risk across institutional settings. It builds on previous research that dealt with the impact of labour market reform measures on the distribution of labour market risks in advanced economies. It is widely held that such reforms have a particularly adverse effect on labour market outsiders, specifically on entrants to the labour market. We seek to differentiate this assumption and to show that this presumed effect is conditional on the configuration of the bargaining system. Using hierarchical models that match EU Statistics on Income and Living Conditions (EU-SILC) microdata with several macro indicators for 20 countries, we find that, in contexts with a high degree of bargaining centralization, the relative low-wage risk of entrants and re-entrants from inactivity increases with commodification and deregulation. If bargaining is decentralized, however, the effects of labour market reform policies on insider/outsider disparities are marginal. Additionally, we show that the same still holds true if a measure of employment protection legislation (EPL) is regarded as the moderating institutional filter. We explain these findings with theoretical concerns based on the concept of closure. These predict that centralized bargaining structures and high EPL (or, rather, closed employment relationships) will systematically channel risks produced by reform measures to the periphery of the labour market.
Additional information: This is a pre-copy-editing, author-produced PDF of an article accepted for publication in European Sociological Review following peer review. The definitive publisher-authenticated version The Impact of Labour Market Reform Policies on Insiders' and Outsiders' Low-Wage Risk / Marco Giesselmann. In: European Sociological Review 30 (2014), 5, p. 549-561 is available online at: http://dx.doi.org/10.1093/esr/jcu053
Keywords: 330; Arbeitsmarktpolitik; Lohn; Gehalt; Niedriglohn